Allozyme variation between South American geographic populations of Microctonus hyperodae - Iline, I.I.; Phillips, C.B.; Goldson, S.L.; Chapman, H.M. (New Zealand Plant Protection, 2002)
Eight South American geographic populations of the parasitoid Microctonus hyperodae Loan (Hymenoptera Braconidae) have been released in New Zealand to help suppress the pasture pest Listronotus bonariensis (Kuschel) (Colepotera Curculionidae) Parasitoids from each South American population were released in equal numbers throughout New Zealand It was postulated that the population(s) best suited to the conditions encountered at each New Zealand release locality would eventually become prevalent there Genetic markers which will enable the South American populations that have become successful in New Zealand to be identified are being developed and this paper reports a preliminary assessment of M hyperodae allozyme variation Malate dehydrogenase (MDH) was the only variable enzyme of the six that were assayed and it exhibited variation consistent with the presence of two alleles All parasitoids from east of the Andes (Argentina Brazil and Uruguay) were heterozygous (MDHa/MDHb) while all those from the west (Chile) were homozygous (MDHa/MDHa) This corroborates earlier morphometric evidence of genetic differentiation between South American populations and indicates that work with additional enzymes should yield more markers